INEL Enets Corpus - Shluinsky, Andrey; Khanina, Olesya; Wagner-Nagy, Beáta (2024)
Corpus Citation Shluinsky, Andrey; Khanina, Olesya; Wagner-Nagy, Beáta. 2024. INEL Enets Corpus. Version 1.0. Publication date 2024-11-30. https://hdl.handle.net/11022/0000-0007-FE1D-C. Archived at Universität Hamburg. In: The INEL corpora of indigenous Northern Eurasian languages. https://hdl.handle.net/11022/0000-0007-F45A-1 Corpus Description The INEL Enets corpus has been created within the long-term INEL project ("Grammatical Descriptions, Corpora and Language Technology for Indigenous Northern Eurasian Languages"), 2016–2033. The corpus includes texts recorded between 1962–2017 in both Enets lects – Forest Enets and Tundra Enets. The sources of the corpus (see more details in the user documentation, section 2.2) are: Audio recordings done by Olesya Khanina, Maria Ovsjannikova, Andrey Shluinsky, Natalia Stoynova and Sergey Trubetskoy, Legacy audio recordings done by Vera Bettu, Nina N. Bolina, Dar`ya S. Bolina, Zoya N. Bolina, Oksana E. Dobzhanskaya, Valentin Gusev, Eugene Helimski†, Kazimir I. Labanauskas†, Larisa Leisiö, Marina Lyublinskaya, Kaur Mägi, Viktor N. Pal`chin, Marina N. Pal`china, Irina P. Sorokina†, Anna Urmanchieva, Beáta Wagner-Nagy and possibly other people, Published audio recordings, Texts published by Dar`ya S. Bolina, Yaroslav A. Gluxij† and Vasilij A. Susekov†, Eugene Helimski†, Kazimir I. Labanauskas†, Tibor Mikola†, János Pusztay, Irina P. Sorokina†, Anna Urmanchieva, Legacy manuscript transcriptions and self-transcriptions done and/or edited by Dar`ya S. Bolina, Galina S. Bolina, Zoya N. Bolina, Valentin Gusev, Eugene Helimski†, Kazimir I. Labanauskas†, Larisa Leisiö, Marina Lyublinskaya, Vasilij F. Ly`rmin†, Anton N. Pal`chin, Viktor N. Pal`chin, Ivan I. Silkin†, Irina P. Sorokina†, Natal`ya M. Tereščenko†, Anna Urmanchieva and possibly other people. All texts in the corpus are provided with interlinear morpheme-by-morpheme glosses and translation into English and Russian. All texts for which the audio recordings were accessible are time-aligned with them. Video recordings are ...